Performance of State-Owned Enterprises: A Comparative Analysis of Ethiopian Airlines and Ghana Airways - Andoh, Samuel K.; Gebremariam, Yilma; Thorson, James; Bodo, Peter (American Journal of Management, 2019)
This paper examines the performance of two state-owned airlines: Ethiopian Airlines and Ghana Airways. While Ethiopian Airlines continues to operate successfully, the other airline has gone out of business. In an industry characterized by heavy competition and a high rate of failure, the success of the state- owned Ethiopian Airlines is intriguing. The evidence shows that Ethiopian Airlines outperforms the industry on some important benchmarks. These findings suggest that being a state enterprise is not necessarily a characteristic that leads to failure. Corporate culture and governance appear to be important factors in the success of Ethiopian Airlines.
Num Pages: 141-156 Place: West Palm Beach, United States
Keywords: Airlines; Business And Economics–Management; Business metrics; Economic growth; Economic theory; Emerging markets; Failure; Profits; Public enterprise; Stockholders; Success; dept.eco; peer-reviewed; ⛔ No DOI found